SIGNS OF SOLID STATE CHARACTERISTICS OF INTRUSION OF KONDER MASSIF AND THE PROBLEM OF MANTLE DIAPIRISM - Lazarenkov V.G.; Landa E.A. (My University, 1992)
An examination was made of the geological, textural-structural, mineralogical and geochemical signs indicating that the dunites forming the Konder massif were in the solid phase during their intrusion into the upper layers of the crust. These signs are metamorphogenic textures and flow structures, cleavage in olivine, olivine-chromspinellid and chromspinellid-isoferroplatinum diffusion borders, thin-layered cleavage, the distribution characteristics, the trace elements and rare earth elements and others. Two models of the ascent of ultrabasic mantle diapirs are discussed.